2014
DOI: 10.4028/www.scientific.net/amr.984-985.740
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Offshore Wind and Seashore Wave Farm Fed to a Power Grid Using a UPFC

Abstract: This project presents the analyzed results of an integrated offshore wind and seashore wave farm fed to an onshore power grid through a unified power flow controller (UPFC) to simultaneously achieve power-fluctuation mitigation and stability improvement. A damping controller of the proposed UPFC is designed by using modal control theory to render adequate damping characteristics to the studied system. A frequency-domain scheme based on a linear system and a time-domain scheme based on a nonlinear system. From … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Since this combination does not require any technological development due to the utilisation of developed technologies, it will only need suitable grid planning and integration. There are some studies that discuss combined wave and wind energy utilisation for electricity production and grid integration [87, 126, 142–148]. In [126], the output power variations of combined wind and wave farms are analysed, and it is demonstrated that combined utilisation is better than an individual wave or wind farms, according to the reserve requirements.…”
Section: Combinational Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this combination does not require any technological development due to the utilisation of developed technologies, it will only need suitable grid planning and integration. There are some studies that discuss combined wave and wind energy utilisation for electricity production and grid integration [87, 126, 142–148]. In [126], the output power variations of combined wind and wave farms are analysed, and it is demonstrated that combined utilisation is better than an individual wave or wind farms, according to the reserve requirements.…”
Section: Combinational Studiesmentioning
confidence: 99%
“…Alex et al. [147] present a similar approach to that of Wang et al., and presented UPFC with a damping controller‐based grid connection, for a combined wind and wave farm, concluding that the given combination achieves dynamic stability and mitigation of power variations. A DC microgrid consisting of both wave and wind energy is proposed by Lu et al.…”
Section: Combinational Studiesmentioning
confidence: 99%